2014
DOI: 10.1038/ncb3058
|View full text |Cite
|
Sign up to set email alerts
|

A cell-intrinsic role for TLR2–MYD88 in intestinal and breast epithelia and oncogenesis

Abstract: It has been postulated that there is a link between inflammation and cancer. Here we describe a role for cell-intrinsic toll-like receptor-2 (TLR2; which is involved in inflammatory response) signalling in normal intestinal and mammary epithelial cells and oncogenesis. The downstream effectors of TLR2 are expressed by normal intestinal and mammary epithelia, including the stem/progenitor cells. Deletion of MYD88 or TLR2 in the intestinal epithelium markedly reduces DSS-induced colitis regeneration and spontane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
99
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(117 citation statements)
references
References 66 publications
17
99
0
1
Order By: Relevance
“…Consistent with these findings, it has been shown that TLR2 signaling in cancer cells plays a tumor-promoting role through the enhancement of stemness (23,24). Moreover, the epithelial cell-specific deletion of Myd88 was observed to suppress intestinal tumorigenesis in Apc Min mice (16). These results suggest that the TLR2/CD14 signaling in "epithelial cells" promotes tumor development through the maintenance of the undifferentiated status of tumor cells.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Consistent with these findings, it has been shown that TLR2 signaling in cancer cells plays a tumor-promoting role through the enhancement of stemness (23,24). Moreover, the epithelial cell-specific deletion of Myd88 was observed to suppress intestinal tumorigenesis in Apc Min mice (16). These results suggest that the TLR2/CD14 signaling in "epithelial cells" promotes tumor development through the maintenance of the undifferentiated status of tumor cells.…”
Section: Discussionsupporting
confidence: 75%
“…On the other hand, the NF-kB pathway is activated in both differentiated (tubular type and papillary type) and undifferentiated (mucinous type) human gastric cancers, which suggests that the MyD88/NF-kB pathway is Table S2). The expression of Tlr2 and Cd14 in intestinal and mammary epithelial cells is associated with the activation of Wnt signaling, which may explain the increased stemness and tumorigenicity (16). We herein showed that Wnt/b-catenin signaling is significantly suppressed and that differentiation is induced in gastric tumors by Myd88 disruption, supporting the idea that TLR2/CD14 signaling enhances the stemness of tumor cells through activation of Wnt signaling.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In accordance, Tlr2 and Tlr4 were found to regulate the proliferation of intestinal stem cells and of Lgr5 expression, even though the effects were reported to be mediated either by the adapter Trif 28 or MyD88. 29 Of note, expression of MyD88 in myeloid cells was sufficient to induce expression of the transcription factor Slug , a master-induced of epithelia-mesenchymal transition, indicating that signaling factors released by macrophages induce EMT.…”
Section: Discussionmentioning
confidence: 99%